Pelaksanaan Strategi Pemasaran Dalam Meningkatkan Usaha PT. Aerofood ACS - Surabaya - Liany Fari Adellia Maharani; Sonja Andarini (Politeknik Kampar, 2023)
This study uses qualitative research. While the type of research used is descriptive method. The research location is at PT. Aerofood ACS - Surabaya. Descriptive method, namely researchers who are intended to collelct information about an existing phenomenon. The research subjelct is the marketing department at PT. Aerofood ACS - Surabaya. Data collelction was carried out by means of observation, interviews and documentation.The results showed that the right marketing strategy to market products at PT. Aerofood ACS - Surabaya is still maintaining the conventional marketing strategy. That is one way to offer or sell services and goods offine or meet each other so that you will meet directly with customers, one of which is through exhibitions or exhibitions.Based on the research resuts, it can be concluded that several strategy developments are the Sales Call strategy: face-to-face meetings between sales representatives and potential customers (or clients) that have been arranged beforehand with the aim of selling products or services. Canvassing strategy is a planned set of individual activities for offering, distributing, and seeking sales orders for products.